Relationship between Poverty and Risky Sexual Behaviours among Adolescents in Rivers State, Nigeria: A Questionnaire – Based Survey - Ezekiel, Rosemary; Madume, Anelechi Kenneth; Kua, Paul Ledee; Ogolodom, Michael Promise; Paul, John Nwolim; Woko, Confidence Nkeiruka; Nweke, Chinoso Vincent (European Scientific Journal, ESJ, 2023)
Background: Adolescents are sexually active and tend to initiate sexual activity at an early age; this has remained a public health concern due to the associated reproductive health risks. , This study was designed to evaluate the relationships between poverty and risky sexual behavior among senior secondary school students in Rivers State, Nigeria. Materials and Methods: A questionnaire-based survey was conducted among 823 students from selected senior secondary schools of Rivers State, Nigeria. The questionnaire consists of two section A and section B and was designed in hardcopy, and distributed to the respondents using one-to one method with the aid of research assistants. The respondent’s consent was duly sought and obtained. The respondent’s private information was treated with confidentiality. Obtained data were exported into Excel software version 2007 and the analysis was done with computer software package, SPSS version 21.0(IBM Corp, Armonk, NY, USA, 2012). Descriptive statistics showing the frequencies and percentages were used to explain the data as appropriate and inferential statistic (Binary Logistic regression) was used to determine the association between poverty and risky sexual behaviour of adolescents. A p value less than 0.05 was set as level of statistical significance. Results: The result of the study indicated that the majority 698(86.6%) of the respondents who reported high poverty engaged in risky sexual behaviour compared to 5(2.69%) of those who reported low poverty. The full model as a whole showing the chi-square analysis result revealed a significant association between poverty and sexual behaviour (χ2 (1, N=823) =3465, P< 0.001). The result of the study further demonstrated that those who indicated been poor were 3.27 times more likely to have sexual intercourse compared to those without peer pressure (OR=3.27, 95%CI: 2.22-4.81). Conclusion: There was significant association between poverty and sexual behaviour and that those who indicated been poor were 3.27 times more likely to have sexual intercourse compared to those without peer pressure.